2021
DOI: 10.1093/jac/dkab299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraosteoblastic activity of dalbavancin against Staphylococcus aureus in an ex vivo model of bone cell infection

Abstract: Objectives Long-acting lipoglycopeptides are promising therapeutic options in Staphylococcus aureus bone and joint infections (BJIs). This study evaluated the ability of dalbavancin to eradicate the intraosteoblastic reservoir of S. aureus, associated with BJI chronicity. Methods Osteoblastic cells were infected with a standardized inoculum of the S. aureus reference strain HG001 and incubated for 24 h with dalbavancin, vanco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In comparison with newer contenders like dalbavancin and rifamycins, Pep16 showcased remarkable intracellular activity. Chauvelot et al 11 showed that dalbavancin, a recently introduced extended-duration lipoglycopeptide, significantly reduced the presence of S. aureus in osteoblasts starting at its MIC (0.125 mg/L), demonstrating a dose-dependent effectiveness. However, Pep16 outperformed dalbavancin, achieving reductions of 86.6% for MRSA isolates and approximately 63% for MSSA isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with newer contenders like dalbavancin and rifamycins, Pep16 showcased remarkable intracellular activity. Chauvelot et al 11 showed that dalbavancin, a recently introduced extended-duration lipoglycopeptide, significantly reduced the presence of S. aureus in osteoblasts starting at its MIC (0.125 mg/L), demonstrating a dose-dependent effectiveness. However, Pep16 outperformed dalbavancin, achieving reductions of 86.6% for MRSA isolates and approximately 63% for MSSA isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the peak of reduction by dalbavancin at 100× its MIC was only 51.6%. 11 In another study, conducted by Abad et al 19 on rifamycins, a group of antibiotics that inhibit bacterial RNA polymerase, the potential intracellular activity of these drugs against S. aureus was highlighted. When examining concentrations that were 10× or 100× their respective MICs, all rifamycins exhibited significant intracellular activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of S. aureus bone tissue infection, the types of intracellular colonization mainly involved osteoblasts, chondrocytes, synovial endothelial cells, and macrophages, as has been reported in numerous studies [25][26][27]. However, in the PJI model, the dominant cell types that are colonized by S. aureus cells were not clear, and it was unknown whether the presence of antibiotics affected the types of cells that were colonized.…”
Section: Identification Of the Cell Types Colonized By Intracellular ...mentioning
confidence: 98%
“… 5 This is consistent with in vitro data, whereby dalbavancin was significantly more effective at reducing cultivable S. epidermidis from biofilms compared with vancomycin. 6 The pharmakokinetic properties with exceptionally long half-life of dalbavancin (149–250 h) 1 together with clinically relevant synovial and bone concentrations including intra-osteoblastic activity 7 , 8 and a favourable safety profile 9 , 10 render dalbavancin an attractive option for prolonged outpatient antibiotic treatment of implant-associated orthopaedic infections such as prosthetic joint infection (PJI) or fracture-related infection. 2 …”
Section: Introductionmentioning
confidence: 99%